The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1104/pp.114.243824
|View full text |Cite
|
Sign up to set email alerts
|

FRIENDLY Regulates Mitochondrial Distribution, Fusion, and Quality Control in Arabidopsis

Abstract: Mitochondria are defining components of most eukaryotes. However, higher plant mitochondria differ biochemically, morphologically, and dynamically from those in other eukaryotes. FRIENDLY, a member of the CLUSTERED MITOCHONDRIA superfamily, is conserved among eukaryotes and is required for correct distribution of mitochondria within the cell. We sought to understand how disruption of FRIENDLY function in Arabidopsis (Arabidopsis thaliana) leads to mitochondrial clustering and the effects of this aberrant chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 103 publications
8
102
1
Order By: Relevance
“…Using a stable double-transgenic line expressing mito-GFP and the F-actin binding protein reporter mCherry-mTalin (El Zawily et al, 2014), we were able to observe a filamentous and dynamic F-actin cytoskeleton after 24 h of imbibition at 4°C, even though the mitochondria remained relatively immobile (Figure 3; Supplemental Movie 3). The F-actin cytoskeleton was more clearly defined against the background fluorescence at later stages of stratification and during germination, exhibiting a similarly dynamic filamentous network at the TR stage as observed at 24 h ( Figure 3A; Supplemental Movie 3).…”
Section: Mitochondrial Immobility During Early Germination Is Not Duementioning
confidence: 91%
See 1 more Smart Citation
“…Using a stable double-transgenic line expressing mito-GFP and the F-actin binding protein reporter mCherry-mTalin (El Zawily et al, 2014), we were able to observe a filamentous and dynamic F-actin cytoskeleton after 24 h of imbibition at 4°C, even though the mitochondria remained relatively immobile (Figure 3; Supplemental Movie 3). The F-actin cytoskeleton was more clearly defined against the background fluorescence at later stages of stratification and during germination, exhibiting a similarly dynamic filamentous network at the TR stage as observed at 24 h ( Figure 3A; Supplemental Movie 3).…”
Section: Mitochondrial Immobility During Early Germination Is Not Duementioning
confidence: 91%
“…Visualization of mitochondria was performed using transgenic lines expressing mGFP5 (Siemering et al, 1996) or mCherry (Shaner et al, 2004) targeted to the mitochondrial matrix (mito-GFP [Logan and Leaver, 2000] or mito-mCherry [Candat et al, 2014]). In order to visualize actin filaments and mitochondria, a double transgenic line was used expressing mito-GFP and an in-frame fusion of mCherry to the actin binding domain of mouse talin (El Zawily et al, 2014;Kost et al, 1998). The endoplasmic reticulum was observed in a line expressing YFP-HDEL (Saint-Jore et al, 2002;Teh and Moore, 2007), while peroxisomes were observed in a line expressing YFP-SKL (Mathur et al, 2002).…”
Section: Plants Materials and Growth Conditionsmentioning
confidence: 99%
“…Whether or not mitochondrial arrest is a consequence of the structural ER reorganization remains to be determined. In Arabidopsis, clustering and immobilization of mitochondria has been observed in response to UV light exposure (Gao et al, 2008) or upon application of methyl jasmonate , the oxylipin 9-hydroxy-10,12,15-octadecatrienoic acid (Vellosillo et al, 2013), or reactive oxygen species (ROS) (Scott and Logan, 2008) and was suggested to be controlled by the CLUSTERED MITOCHONDRIAtype FRIENDLY gene product (El Zawily et al, 2014). Thus, it will be interesting to test friendly mutant plants in regard to pathogeninduced mitochondrial arrest, PEN2 recruitment patterns, and subsequent disruption of pathogen entry resistance.…”
Section: Discussionmentioning
confidence: 99%
“…So far, CLU deficiency induces mitochondrial clustering in all organisms tested, including the protist Dictyostelium discoideum (Fields et al, 2002;Zhu et al, 1997), the yeast Saccharomyces cerevisiae (Fields et al, 1998), the plant Arabidopsis thaliana (El Zawily et al, 2014;Logan et al, 2003) and the animal Drosophila melanogaster (Cox and Spradling, 2009), as well as mouse embryonic fibroblasts (Gao et al, 2014) and human cancer cells (Gao et al, 2014). While CLU function is clearly required to prevent mitochondrial clustering, the mechanism responsible remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Fields et al reported that in cluA -Dictyostelium cells, mitochondria were connected to neighboring mitochondria through narrow constrictions, suggesting impaired fission (Fields et al, 2002). However, in Arabidopsis, mutations in the CLU family gene FRIENDLY do not cause constrictions, but instead lead to increased association time during the mitochondrial fusion process, which was reported to favor clustering (El Zawily et al, 2014). In Drososphila, the CLU ortholog clueless interacts genetically (Cox and Spradling, 2009) and physically with the PINK1-Parkin pathway (Sen et al, 2015), to promote Valosin-Containing Protein (VCP)-mediated Marf degradation during the Parkindependent mitophagy (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%